INCIDENCE OF FUSARIUM DISEASE IN STRAWBERRY FIELDS IN TASHKENT REGION - Eshmurzaev Jasur Elmuratovic,; Zuparov Mirakbar Abzalovich, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The article presents the data on the prevalence, severity and development of fusarium disease in strawberries grown in the fields of Tashkent region. The symptoms of this disease in strawberries are explained in detail. The impact of precipitation and temperature on the incidence of fusarium is revealed here in.